Comparison of Vaginal Hysterectomy Techniques and Interventions for Benign Indications: A Systematic Review. Issue 9 (September 2017) - Jeppson, Peter C.; Balgobin, Sunil; Rahn, David D.; Matteson, Kristen A.; Dieter, Alexis A.; Ellington, David R.; Aschkenazi, Sarit O.; Grimes, Cara; Mamik, Mamta M.; Balk, Ethan M.; Murphy, Miles
Abstract : (Abstracted from Obstet Gynecol 2017;129:877–886) Barriers to performing a vaginal hysterectomy (VH) include potential complications, technical difficulties, lack of experience, and low-volume caseload. Increased knowledge is needed about factors associated with success and failure of a vaginal approach.